The Influence of Characteristics of Islamic Human Resources on Employee Performance at Raudlatul Jannah Islamic School Sidoarjo City - Safira, Rana Izza; Canggih, Clarashinta (Universitas Nahdlatul Ulama Sidoarjo, 2025)
The purpose of this research is to find out how human resource characteristics which include the characteristics of the Prophet Muhammad namely Shiddiq, Amanah, Tabligh, and Fatanah on the performance of employees in Islamic School Raudlatul Jannah Sidoarjo. The data used is primary data obtained from the questionnaire and the sampling technique used purposive sampling with a set of 70 people. This research used a quantitative approach, with analysis techniques used as a validity and reliability test, classic assumption test, multiple linear regression analysis, t-test, and coefficient of determination test. The study's findings clarify that employee performance is unaffected by Siddiq and Tabligh's human resources characteristics. The influence of characteristics of the Prophets Muhammad are Amanah and Fatanah influence employee performance. There is a close relationship between the quality of human resources and performance that determines a company's success. Educational institutions, especially those that produce the nation's generation, are determined by the educators in them. Qualified educators are needed, and they must have Islamic characteristics so that they can provide high performance.